The assessment of water purification quality characteristics (WPQC), water quality index (WQI), and their measurement techniques, arid region of Rawalpindi, Pakistan - Ali, Muhammad Qasim; Alam, Waheed; Talib, Aqib; Ali Naveed, Mirza Hamza; Afzal, Muhammad Waqas; Jabbar, Abdul; Zahoor, Basharat; Noormazlinah, Ahmad (European Chemical Bulletin, 2023)
Drinking water quality is essential for public health. With the aid of the water quality index, the current research investigation aimed to monitor the quality of drinking water and assess the action of water purification plants in the surrounding areas of PMAS Arid Agriculture University Rawalpindi (WQI). A total of 150 water samples be situated gathered from 20 water purification plants. The pH, EC, TDS, free chlorine turbidity, total hardness, cations (Na, K, Ca, and Mg), anions (Cl, HCO3, SO4, NO3, and F), manganese, iron, and total hardness of drinking water were all analyzed. In terms of the assessed physicochemical character, the results showed that purified water was acceptable for consumption. The overall water purification efficacy for reducing total dissolved salts and related anions and cations was greater than 90%. TDS levels in groundwater averaged 1919 ± 806 mg/L but were reduced to 119 ± 32.9 mg/L in purified water. According to the water quality index, all filtered water samples were of high drinking quality (class I). Meanwhile, due to many dissolved salts, 80.6 percent of the contaminated groundwater sample was of poor drinking quality (class III), and 10.9 percent was of extremely poor drinking quality (class IV). Groundwater filtration improved the water quality from extremely low to poor (classes III and IV) to good (class I)